FRI0468-HPR What does the language we use about arthritis mean to a patient?. (23rd January 2014) - Barker, K.; Minns Lowe, C.; Reid, M.
Abstract : Background: Research shows that more than 80 percent of patients have poor health literacy. To date, research has focussed on language associated with back pain, with less on general musculoskeletal complaints, although these account for a large amount of physiotherapy consultations. Objectives: To determine patients' knowledge, awareness and comprehension of the language used to describe arthritis, including gaining feedback on the emotional impact of the terms. Methods: Five qualitative focus groups of 6-8 respondents, and 6 individual in-depth interviews were conducted among a purposive sample of: Men and women (50/50 split across the sample); patients aged 45 years and over with a spread of ages in each group and within the overall sample of depth interviews and a range of socio-economic groupings. Key terms such as arthritis, degenerative, rheumatism, wear and tear and rehabilitation were used as stimulus materials. Focus groups and interviews were audio-recorded, transcribed verbatim and underwent line by line coding and thematic analysis using interpretative phenomenological analysis. Results: Patients were familiar with many of the terms such as arthritis, osteoarthritis, rheumatism, inflammation etc, but their level of comprehension varied. Most terms had little emotional impact. Terms used to describe pathophysiology such as "wear and tear" and "degenerative" elicited negative emotional impact, especially in women. Terms such as rehabilitation and "self management" were poorly understood and produced negative emotional impact. Conclusions: Health care professionals should not assume that patients' familiarity with medical terms correlate to understanding the term. They should be aware of the potential for negative emotional impact related to some terms. Disclosure of Interest: None Declared